Analysis of Earnings Management Practices and Sustainability Reporting for Corporations that Offer Islamic Products & Services - Mohd Sabrun, Ibrahim; Faizah, Darus; Haslinda, Yusoff; Rusnah, Muhamad (Elsevier B.V., 2015)
Earnings management is generally viewed as unethical behaviour as it involves the use of managerial discretion of accounting numbers, which may result in the distortion of financial information provided to stakeholders. However, the engagement in socially responsible initiatives by companies demonstrates their concern for the societal well-being which goes beyond profit making. The aim of this study is to examine the earnings management practices and sustainability reporting among corporate sectors that offer Islamic products. An Islamic perspective is used to underpin the theoretical arguments for this study. This study uses longitudinal panel data analysis to examine the sustainability reporting of 16 public-listed companies in Malaysia that offer Islamic financial products for a three year period from 2011 to 2013. Content analyses on corporate annual and stand-alone reports used Global Reporting Initiatives (G3) guidelines to measure the quality of the sustainability disclosure, while the earnings management related data was obtained using the Modified Jones Model. The results of the study provide evidence that the sustainability reporting practices among companies in Malaysia that offer Islamic products are generally good over the three-year period and that financial performance improved the quality of sustainability reporting. The insignificant results between earnings management and the quality of sustainability reporting suggest that sustainability reporting is not being manipulated to cover their earnings management practices.